FPGA Implementation of AHB to APB Protocol (International Journal of Engineering and Computer Science, 2017)
The field of technology is evolving at a very fast pace. The competition is very intense. So the need of the hour is to produce efficient system. In accomplishing this objective we are required to establish better interaction among all the components of the system. This requirement is fulfilled by the Advanced Microcontroller Bus Architecture (AMBA) protocol from Advanced RISC Machines (ARM).The AMBA is the on-chip standard for the communication among components in Application Specific Integrated Circuits (ASIC) or System on Chip (SoC). This paper focuses on the 2 protocols of AMBA which are Advanced High Performance Bus (AHB) and Advanced Peripheral Bus (APB) and the APB bridge.  The coding is done in Verilog synthesis on Xilinx 14.7 ISE and simulation on ISim simulator and FPGA implementation on Spartan 3.